2015
DOI: 10.1016/j.phrp.2015.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Head Lice Infestation and Its Associated Factors among Primary School Students in Iran: A Systematic Review and Meta-analysis

Abstract: ObjectivesHead lice infestation is one of the most important health problems, generally involving children aged 5–13 years. This study aims to estimate the prevalence of head lice infestation and its associated factors among primary school children using systematic review and meta-analysis methods.MethodsDifferent national and international databases were searched for selecting the relevant studies using appropriate keywords, Medical Subject Heading terms, and references. Relevant studies with acceptable quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
67
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(90 citation statements)
references
References 26 publications
18
67
4
1
Order By: Relevance
“…This finding is supported by other studies in the northwest of Iran [9, 14]. Similarly, in studies conducted in Korea, Jordan, and Egypt, a strong association between head lice infestation and bathing facilities in the home was reported [1517].…”
Section: Discussionsupporting
confidence: 83%
“…This finding is supported by other studies in the northwest of Iran [9, 14]. Similarly, in studies conducted in Korea, Jordan, and Egypt, a strong association between head lice infestation and bathing facilities in the home was reported [1517].…”
Section: Discussionsupporting
confidence: 83%
“…It shows that the better behavior could better improve prevention of Pediculosis capitis. It is in line with the study which stated that behavioral factors have an association with the Pediculosis capitis infection [16]. A positive response towards the prevention is based on the awareness that Pediculosis capitis is a problem that affect the daily activities, this is evidence by the responses where they agreed that they are willing to prevent and treat Pediculosis capitis because they feel uncomfortable and itchy of the scalp.…”
Section: Discussionsupporting
confidence: 78%
“…The result of identification data which seven respondents with good knowledge, showed that they did not aware to prevent using stuffs together such as veil, headband, clothes, comb, towel, and bad habit in washing and drying clothes. It correspond with a study regarding factors related to the prevalence that using common comb can cause the Pediculosis capitis [16]. The bedroom was 3x5 meter filled 20-23 students, students sleep together by sharing bed stuffs.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The extensive use of pediculicides with a neurotoxic mode of action has led to the development and spread of resistant head lice populations worldwide [12][13][14]. In addition, the failure of current chemical treatments to kill lice embryos in eggs, the environmental and food safety concerns posed by these treatments, and their potential toxicity to users necessitate the development of safe alternative treatment methods that can effectively kill adult lice and eggs via new modes of action [15,16], Other causes for the development of resistance to existing pediculicides include the persistence of pediculicide residue on hair, exposure of lice to sub-therapeutic concentrations, and inadequate concentration levels [5,6]. Numerous studies of the different types of head lice treatments have revealed that commercial pediculicides are ineffective in treating head lice infestations in students [12][13][14][17][18][19].…”
Section: Discussionmentioning
confidence: 99%